Pengaruh Motivasi, Disiplin Kerja Dan Lngkungan Kerja Terhadap Kinerja Karyawan (Pada Rumah Sakit Umum Daerah Ngimbang, Lamongan, Jawa Timur) - Shinta Devia Frimadani; Hadi Sunaryo; Arini Fitria Mustapita (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThis research was conducted to determine the effect of motivation, work discipline and work environment on the performance of nurses (at the Ngimbang Regional General Hospital, Lamongan, East Java). This research uses explanatory research and a quantitative approach. Arikunto's theory is used to take samples, that is, the population is less than 100, so the entire population is taken as a sample, so this research is called saturated sample or census research. The sample in this study included all nurses at Ngimbang Hospital, Lamongan, East Java, totaling 90 nursesTo solve the problem in this study, using the validity test, reliability test, normality test, multiple linear regression test, multicollinearity test, heteroscedasticity test, classical assumption test. The study used multiple linear regression analysis with the help of SPSS 20. The results of this study were simultaneously the variables of Work Motivation, Work Discipline and Work Environment on Nurse Performance at the Ngimbang Regional General Hospital, Lamongan, East Java, the work motivation variable partially had a positive and significant effect. on the performance of nurses at the Ngimbang Regional General Hospital, Lamongan, East Java, the variable work discipline partially has a positive and significant effect on the performance of nurses at the Ngimbang Regional General Hospital, Lamongan, East Java, the work environment variable partially has a positive and significant effect on performance. Nurse at Ngimbang Regional General Hospital, Lamongan, East Java Keywords: Nurse Performance, Motivation, Work Discipline, Work Environment